Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Augmented Reality Terhadap Peningkatan Pemahaman Konsep dan Minat Belajar Peserta Didik pada Materi Cermin Cembung : Penelitian - Moh. Farhan Fuad; Arin Wildani; Suprianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the effect of a guided inquiry learning model assisted by Augmented Reality on students’ conceptual understanding and learning interest regarding convex mirror material. Using a quasi-experimental quantitative design, two groups were compared: an experimental class using guided inquiry with Augmented Reality and a control class using direct instruction. Normality and homogeneity tests indicated that the data met parametric test assumptions (p > 0.05). The t-test showed a significant difference in conceptual understanding between the groups (p = 0.000). The experimental group achieved a higher N-Gain score (0.67, moderate) than the control group (0.25, low), with an effect size of 2.058, indicating a strong impact. Additionally, student interest responses reached 90% (very high category). Overall, guided inquiry learning assisted by Augmented Reality proved effective in improving students’ conceptual understanding and learning interest in physics.